A novel time-resolved fluoroimmunoassay based on magnetic microspheres method for detecting antibodies against the phospholipase A2 receptor. Issue 27 (24th June 2021) - Li, Ting; Wu, Qingqing; Yang, Xue; Liu, Yueming; Lin, Bo; Zhou, Xiumei; Wang, Yigang; Qin, Yuan; Wang, Binrong; Hu, Zhigang; He, Qiang; Huang, Biao
Abstract : A novel magnetic microsphere-based anti-PLA2R-IgG-TRFIA method is established, which provides a convenient and effective tool to detect the concentrations of anti-PLA2R-IgG in the sera of patients with idiopathic membranous nephropathy. Abstract : Background : the level of serum antibodies against the M-type phospholipase A2 receptor (anti-PLA2R-IgG) is closely related to the disease activity of idiopathic membranous nephropathy (IMN). Therefore, the establishment of a sensitive and rapid method for detecting anti-PLA2R-IgG will be beneficial for the differential diagnosis of IMN. Methods : magnetic microspheres coupled with the PLA2R antigen were used to capture anti-PLA2R-IgG in serum samples, and europium-labeled goat anti-human IgG antibodies were used for tracking. An anti-PLA2R-IgG-time-resolved fluoroimmunoassay (TRFIA) based on magnetic microspheres using an indirect method was established and analyzed. Various indicators of this method were evaluated. Results : the sensitivity of the anti-PLA2R-IgG-TRFIA based on magnetic microspheres was 0.51 RU mL −1, and the linear detection range was 0.51–1000 RU mL −1 . The average intra- and inter-assay coefficients of variation (CVs) were 3.62% and 4.45%, respectively, and the average recovery was 95.60%. No cross-reactivity with IgA was observed. The median (interquartile range) concentration of anti-PLA2R-IgG in patients with IMN was 40.37 RU mL −1 (11.33 to 83.05 RU mL −1 ). The cut-off values of the anti-PLA2R-IgG concentration for healthy volunteers and those with other kidney diseases were determined to be 8.06 RU mL −1 and 13.23 RU mL −1, respectively. Additionally, the positive rates of anti-PLA2R-IgG in patients with IMN corresponding to the above cut-off values were 91.07% and 71.32%, respectively. The correlation coefficient between the magnetic microsphere-based anti-PLA2R-TRFIA and the PLA2R-ELISA kit for detecting anti-PLA2R-IgG was 0.944. Conclusion : a highly sensitive and rapid magnetic microsphere-based anti-PLA2R-IgG-TRFIA was successfully established to detect the concentrations of anti-PLA2R-IgG in the sera of patients with IMN.